Transcatheter aortic valve implantation after previous mechanical mitral valve replacement: Expanding indications? - Beller, Carsten J.; Bekeredjian, Raffi; Krumsdorf, Ulrike; Leipold, Rüdiger Wolfgang; Katus, Hugo; Karck, Matthias; Rottbauer, Wolfgang; Kallenbach, Klaus (The heart surgery forum, 2011)
Background: Cardiac operation for severe aortic stenosis after previous mitral valve replacement is a surgical challenge in older patients with multiple morbidities. Transcatheter aortic valve implantation (TAVI) after previous mechanical mitral valve replacement has been considered a high-risk procedure, owing to possible interference with the mitral valve prosthesis.Methods: Since August 2008, 5 female high-risk patients with severe aortic stenosis and previous mitral valve replacement (mean ± SD age, 80 ± 5.1 years; logistic EuroSCORE, 39.3% ± 20.5%) underwent TAVI with a pericardial xenograft valve that was fixed with a stainless steel, balloon-expandable stent (Edwards Lifesciences SAPIEN). We used a transapical approach in 4 patients and a transfemoral approach in 1 patient. Transesophageal echocardiography and multidetector computed tomography were used for preoperative planning and assessment of operation feasibility. The mean distance between the aortic annulus and the mitral valve prosthesis was 10 ± 1 mm (range, 9-11 mm).Results: TAVI was performed successfully in all 5 patients. There was no direct or functional interference with the mechanical mitral valve prostheses. Echocardiography revealed good valve function with no more than mild paravalvular incompetence early in the postoperative period and during routine follow-up. There were no neurologic events. After an initially uneventful course with good aortic valve function at the most recent echocardiography evaluation, however, 2 of the patients died from fulminant pneumonia on postoperative days 4 and 48.Conclusion: TAVI is technically feasible in high-risk patients after previous mechanical mitral valve replacement; however, careful patient selection is mandatory with respect to preoperative clinical status and anatomic dimensions regarding the distance between aortic annulus and mitral valve prosthesis.
Gesehen am 16.03.2022